Memories of the Future. Ulrich Beck, Risk and Prevention: The Difference that Defeats Indifference - Gavrila, Mihaela; Cilento, Marco (Italian Sociological Review, 2022)
The aim of this contribution is to demonstrate the relevance of Ulrich Beck’s thought with regards to the interpretation of complex phenomena such as the COVID-19 pandemic and the war in Ukraine. In this perspective, the social function of his thought on risk as a way to think about the future and as a strategy for the anticipation of emerging global problems is explored. The reflection on risk as an intrinsic dimension of contemporary societies is associated with the call for the development of a collective and individual future more attentive to the cultivation of empathy, solidarity and a new humanism as a dimension of the solidity of a society.